Morphological diversity and genetic homogeneity in Spondylus squamosus from Lianga Bay, Surigao del Sur, Philippines - FABIO JR. C. RUAZA (Society for Indonesian Biodiversity, 2025)
Abstract. Ruaza FC. 2025. Morphological diversity and genetic homogeneity in Spondylus squamosus (Scheiber, 1703) from Lianga Bay, Surigao del Sur, Philippines. Biodiversitas 26: 1768-1776. This study investigates the two morphotypes of Spondylus squamosus found in the northern and southern parts of Lianga Bay, Surigao del Sur, using landmark-based geomorphometry, Field Emission Scanning Electron Microscopy (FESEM) for shell microstructures, and molecular analysis. The research aims to determine the morphological and genetic differences between the two morphotypes and assess their plasticity and potential evolutionary divergence. Geomorphometric analysis revealed distinct clusters among the morphotypes when projected onto a two-dimensional plane based on their relative warp coordinates, suggesting significant morphological plasticity in shell structure. Despite these differences in external morphology, shell microstructure analysis showed that both morphotypes share the same shell structure, characterized by a regular complex crossed lamellar outer layer composed of long rod-shaped mineral crystals stacked parallel to each other. Molecular analysis using mitochondrial 12S and 16S genes revealed a high percentage of identity, confirming that both northern and southern individuals are S. squamosus. This genetic consistency supports the conclusion that the two morphotypes belong to the same species, despite their morphological variability. The significance of these findings is underscored by their implications for biodiversity preservation and conservation strategies in Lianga Bay. Understanding the ecological dynamics and the role of S. squamosus within the ecosystem provides insights into sustainable management strategies. This study recommends further research into the environmental factors contributing to this morphological diversity, considering the adaptive significance of these differences to provide insights into the evolutionary processes shaping S. squamosus populations.